Math, asked by TANU81, 1 year ago

And True or False ;-
____
√ a+b. = √a +√b
(a+b)² = a²+ 2ab+ b²
(a+b)³ = a³+ 3a²b +3ab²+b³

Please solve

Attachments:

Answers

Answered by Anonymous
19
Heya!!

-----------------------------

True / False :

1. False
2. True
3. True

----------------------------

Hope it helps u :)
Attachments:

TANU81: Thanks ☺️☺️
Anonymous: 5th thnk? :D.. my pleasure sista!
Answered by rohitkumargupta
12
HELLO DEAR,



★ ( 1 ) ★

sum of roots = 5/3

product of roots = 4


general formula for finding quadratic equations,

x² - (sum of roots)x + (product of roots) = 0

x² - (5/3)x + (4) = 0

3x² - 5x + 12 = 0




VERIFICATION:-


sum of roots = -b/a

5/3 = -(-5)/3

=> 5/3 = 5/3

product of roots = c/a

4 = 12/3

=> 4 = 4




★ ( 2 ) ★


given that:-

" 2 " is the zeroes of the polynomial

it means the valus of x = 2 put in the equation,

we get,

(k - 1)x² + 2x + 5 = 0

=> (k - 1)(2)² + 2(2) + 5 = 0

=> 4k - 4 + 4 + 5 = 0

=> 4k = -5

=> k = -5/4



VERIFICATION:-


put the value of "k" & "x" in the Equation,

(-5/4 - 1)(2)² + 2(2) + 5 = 0

=> (-5 - 4)/4 * 4 + 4 + 5 = 0

=> -9 + 9 = 0



★ ( 3 ) ★

x² - 7x + 10

x² - 5x - 2x + 10

x(x - 5) - 2(x - 5)

(x - 2)(x - 5)





TRUE  \:  \:  \: AND  \:  \:  \:  \:  FALSE


★ ( 1 ) ★

√(a + b) = √a + √b not possible

it is false,



★ ( 2 ) ★


(a + b)² = (a + b)(a + b)

= (a² + ab + ba + b²)

= (a² + 2ab + b²)

"true"


★ ( 3 ) ★


(a + b)³ = (a + b)² * (a + b)

= (a² + 2ab + b²) (a + b)

= [ a(a² + 2ab + b²) + (b(a² + 2ab + b²)

= (a³ + 2a²b + ab² + a²b + 2ab² + b³)

= (a³ + b³ + 3a²b + 3ab²)

= [ a³ + b3 + 3ab(a + b) ]

"true"



★ I HOPE ITS HELP YOU DEAR,
THANKS★


rohitkumargupta: :-)
TANU81: Nice thx a lot ⚛️
rohitkumargupta: thanks
Similar questions